(untitled) (Acta Scientiarum. Biological Sciences, 2014)
The survival of social wasp species depends on the success in founding new nests. These species can use plant species with different specific characteristics for nesting, with nest architecture varying according to the habits of those plant species. The nesting of social wasps in natural environments was studied in the period from October 2005 to September 2007 inthe rio das Mortes riparian forest, municipal district of Barroso, Minas Gerais State, Brazil, with the objective of evaluating the different types of plant substrate used by social wasps for nesting, and to investigate whether there is a relationship between nest construction type and the habits of plant species. A total of 171 colonies of social wasps belonging to 29 species were recorded, which used 78 plant species as nesting substrate (76 Angiosperms and two Pteridophytes) of arbustive, herbaceous, arboreal, epiphyte and liana habits. Species with phragmocyttarus and gymnodomous nests were observed nesting, with higher incidence, in arboreal plants and their deciduousness did not affect the nesting. The preservation of natural areas is suggested in order to guarantee a higher availability of nesting places for the social wasp species, ensuring their higher efficiency in the environmental services and biological control of agricultural pests.